Effect of processing methods on virgin coconut oil initial and storage quality - Portugues, Judy Alvarez (2006)
ABSTRACT Four virgin coconut oils from different processing methods, namely, fermentation, fermentation with heat, centrifuge and enzymatic were produced and compared for yield, quality and consumer acceptability. The oil samples were also evaluated weekly for its free fatty acid value (FFA), moisture content (MC) as well as sensory attributes to determine any changes in these parameters during a three-week storage at room temperature (26±1°C). In the first phase of the study, significant differences (p<0.05) was found among the four processing methods in terms of overall acceptability, FFA, MC, as well as nutty and acid aromas. Enzymatic process yielded the highest amount of oil and the most acceptable product. The samples were rated from like slightly to like moderately. The FFA values of the virgin coconut oil samples were found to be different, with fermentation process with the highest amount (0.16%) and enzymatic and centrifuge process with the lowest (0.07%). Fermentation process has the highest moisture content (0.19%) among all the VCO samples and centrifuge process has the lowest (0.03%). All of the VCO samples were found to be colorless, no turbidity, perceptible nutty aroma and acid aroma and barely perceptible rancid aroma, except for enzymatic process with moderate nutty aroma. In the second phase of the study, processing methods, storage time and their interactions had significant effects (p<0.05) on the storage quality of VCO in terms of FFA and MC, but not on their sensory characteristics. The panelists perceived that the stored samples were still similar to freshly produced samples. No changes had been observed in color, turbidity, nutty aroma, acid aroma and rancid aroma after three weeks of storage at 26±1?